STUDENT’S RESPONSES TO THE USE OF INSTAGRAM IN TEACHING READING NEWS ITEM TEXT - Yiyis Sunten Anggari; Odo Fadloeli (PROJECT (Professional Journal of English Education), 2021)
The students response is one tool in determining the methods and media of learning, so that it becomes a reference in achieving the success of a learning process. This research was conducted in order to determine the response of students in class XII TKJ 2 Smk Bina Insan Bangsa Ngamprah Bandung, on the use of Instagram in teaching reading news items texts. Thirsty one students were made researchers as research objects, consisting of 14 male students and 17 female students. The data obtained in this study were observation data and questionnaire data of student responses. the method used in this research is descriptive qualitative method, to get the answers to the problems studied. The results revealed  74.8% of students who gave positive responses to the use of Instagram in teaching reading news items texts, because learning activities with the use of Instagram were more interesting, interactive, and fun for students, and as many as 25.2% of students who gave negative responses in the use of Instagram in teaching reading text news items, because there are deficiencies in the use of Instagram, which is related to some students who need difficulties in terms of text content due to lack of vocabulary mastery. Keywords:  Students Responses, Instagram, Reading News Item Text